Safety and Immunogenicity of Increasing Doses of a Clostridium difficile Toxoid Vaccine Administered to Healthy Adults - Kotloff, Karen L.; Wasserman, Steven S.; Losonsky, Genevieve A.; Thomas, William; Nichols, Richard; Edelman, Robert; Bridwell, Margaret; Monath, Thomas P. (Infection and immunity, 2001)
Clostridium difficile is a major cause of nosocomial diarrhea in industrialized countries. Although most illnesses respond to available therapy, infection can increase morbidity, prolong hospitalization, and produce life-threatening colitis. Vaccines are being explored as an alternative means for protecting high-risk individuals. We assessed the safety, immunogenicity, and dose response of a parenteral vaccine containing C. difficile toxoids A and B. Thirty healthy adults were assigned to receive four spaced inoculations on days 1, 8, 30, and 60 with one of three doses of vaccine (6.25, 25, or 100 μg). At each dose level, subjects were randomized, in a double-blind fashion, to receive either the soluble toxoids ( n = 5) or toxoids adsorbed to alum ( n = 5). Subjects were monitored for clinical and immunologic responses to vaccination. Vaccination was generally well tolerated, with occasional, usually mild, systemic reactions (abdominal pain, arthralgia, and diarrhea). The most common local reaction, mild arm pain, was reported by all recipients of the toxoid-alum formulation. Nearly all subjects (≥90%) developed vigorous serum antibody responses to both toxins, as measured by immunoglobulin G (IgG) enzyme-linked immunosorbent assay and neutralization of cytotoxicity, whereas fecal IgA increases occurred in approximately 50%. Statistically significant effects of dose and formulation on immunogenicity were not seen, although antibody levels tended to be higher with the alum-adjuvanted formulations and with increasing doses of soluble toxoid. Serum antibody responses among the toxoid-alum group appeared to plateau at 25 μg. We concluded that the C. difficile toxoid vaccine is safe and immunogenic in healthy volunteers. Further development as a prophylactic vaccine or for producing C. difficile hyperimmune globulin is justified.